Hubungan Self-Confidence dengan Kecemasan Siswa Ketika Bertanya di dalam Kelas - Yusida, Lona Putri; Ibrahim, Indra; Said, Azrul (Konselor, 2014)
Abstract: Braveness in asking question is needed in learning process. By asking question, student is trained to think, to develop information and knowledge, and with frequently asking question, it can increase braveness and confident. However, many students experienced anxiousness in asking question, one of the influences is psychology aspect that is self-confident. This research is purposed to (1) describe students’ self-confident, (2) describe student’s anxiousness while asking question in classroom, and (3) see the relationship between student’s self-confident and anxiety while asking question in classroom. This research is using quantitative approach type descriptive correlation. This research is conducted in VIII and IX class SMPN 13 Padang. Research finding reveal that (1) student’s self-confident tend to to reside in high category, (2) student’s anxiousness while asking question in classroom tend to to reside in low category, (3) there is a significant relationship between students’s self-confident and anxiety while asking question in classroom with high level of correlation.  Keywords: self-confident, anxiety in asking question